Charging Electric Vehicles on Highways: Challenges and Opportunities - Claudio Scarpelli; Massimo Ceraolo; Emanuele Crisostomi; Valerio Apicella; Giulia Pellegrini (IEEE Access, 2024)
As new models of electric vehicles are put on the market, with larger batteries and higher charging rates, there are growing concerns about how the charging infrastructure should be upgraded and modernized to cope with the challenges they pose. Governmental directives and rules dictate minimal requirements for the future charging infrastructure, but would these be enough to handle massive numbers of electric vehicles? In this manuscript we describe an electric mobility simulator that can be used to mimic highway vehicular flows and evaluate the queues at charging stations under different penetration levels of electric vehicles. Based on actual vehicular flows from the most important Italian motorway, we find that non-homogeneous queues at charging stations can be predicted, and the infrastructure planned by the EU rules may not be able to accommodate a penetration level of more than 3% of electric vehicles in the highway without giving rise to unacceptably high waiting times at charging stations. Also, we note that smart assignments of electric vehicles at charging stations may significantly improve waiting times, opening the discussion on the need for allocation policies and guidelines. Extensive Monte Carlo simulations on an accurate reconstruction of the Italian case study support the discussion and our findings.